Inovasi Pembelajaran dalam Penerapan Kurikulum Merdeka di Sekolah Dasar Negeri - Ulfadhilah, Khairunnisa (Academicus: Journal of Teaching and Learning, 2024)
This research aims to understand teachers in implementing the independent curriculum because changing the curriculum will result in learning activities in the classroom, and implementing PAI at Sangkanurip State Elementary School so that learning will be organized and can become a guide for teachers in teaching students. This research method took place at Sangkanurip State Elementary School and then naturalism was used by researchers to find out the results when the research was carried out. Data was obtained during observation, interviews, and documentation as well as data sources during research, namely teachers and school principals. The research results showed that the teacher carried out the initial activities well. The learning process that will be carried out at school, especially in the Merdeka curriculum, teachers must make the learning process interesting, project-based, and flexible in teaching and learning activities, so researchers see that if an evaluation is carried out then the teacher has the ability to assess children's abilities using formative and summative.